Increasing Performance of Treatment Services in the Use of Medical Record Systems - Soeheri Soeheri; Mas Ayoe Elhias Nasution; Rahmad Doni; Juli Iriani (STMIK Pontianak, 2021)
The medical record system is an application that is used in medical services, where with the use of a medical record system, patient data will be stored and arranged neatly for a long time, then with the use of this system it reduces file storage costs and minimizes file storage space. Prior to the use of this medical record system, the midwife supiani clinic was given to record patients by making notes on a patient biographical paper in which the patient's history of treatment and type of illness will be stored. The manual system causes complications in the services provided to patients, because patients will wait very long because the administration will search and unload data if the patient has visited or taken treatment, if he just wants treatment, the administration must look for serial numbers and record the patient's name and biodata. With the medical record system that we provide to the general practice of midwife supian, it is very helpful in terms of data recording, file storage and until services for patients become faster and more efficient. One more thing, the general practitioner midwife supiani can recapitulate in one day anyone who visits for treatment. This is a very large contribution to the general practice of midwives so that they can improve patient treatment services.